A SME self-assessment tool: integrating an impact-& investment scan and a pre-matching platform (A prototype designed by actors of the sustainable finance community) - Koerner, Jana; Heinz, Susanne Mira; Dinesh, Dhanush (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Scaling up sustainable finance in agriculture is limited by several systemic bottlenecks. To address these, CCAFS organized a design thinking series with actors of the sustainable community. This Info Note details the final prototype of the SME self-assessment tool that can help accelerate SME’s investment readiness.